A comprehensive literature review of guidelines facilitating transition of newly graduated nurses to professional nurses. (May 2018) - van Rooyen, Dalena R.M.; Jordan, Portia J.; ten Ham-Baloyi, Wilma; Caka, Ernestina M.
Abstract: Literature shows that successful transition of newly graduate nurses to professional nurses is imperative but does not always take place, resulting in difficulty in performance, cognizance or behaviour of a role as a nurse, affecting the quality of patient care negatively. No integrative literature review could be found to summarize available guidelines facilitating transition of final year nursing students to professional nurses. An extensive search of the literature by means of an integrative literature review was conducted in 2014 and updated in June 2017, following a five-step process. All relevant studies were subsequently appraised for rigour and quality using the AGREE II tool by two independent reviewers. Eight (n = 8) guidelines on transitions were independently extracted. After thematic analysis was done, three factors to facilitate transition of final year nursing students to professional nurses were found: 1) support for new graduates, 2) the graduate's need for socialization and belonging, and 3) a positive clinical learning environment. The availability and implementation of guidelines on transition of final year nursing students by educational institutions and healthcare facilities could ease the transition from being final year nursing students to becoming professional nurses as well as improve retention of newly qualified professional nurses. Highlights: Transition of graduate-to professional nurses is vital but does not always happen. This integrative review summarized guidelines facilitating transition of graduates. Graduates need support, socialization, belonging, and a positive clinical environment. Also, orientation and peer mentor programs and systems of performance are required. Guidelines should be adapted/developed to optimize implementation of the findings.